Socialization Of The Danger Of Cigarette For Passive Smokers At Ratu Samban University Bengkulu - Oktridarti, Levy; Tika, Yori Manis; Astuti, Linda; Shinta, Seftya Dwi; Sumarni, Hania (Jurnal Pengabdian, 2023)
The aim of this outreach is to increase the knowledge and awareness of students at Ratu Samban University, North Bengkulu about the magnitude of the dangers of cigarettes for passive smokers around them. This socialization was attended by 30 students from Ratu Samban University, North Bengkulu. This socialization is carried out by providing material regarding the bad effects of cigarettes on passive smokers and discussions about prevention that can be carried out by the community as a form of prevention so that they are not exposed to passive smoking, namely 1) Avoid gathering with people who smoke by looking for a place that has fresh air free of cigarette smoke, 2) Prohibit people from smoking at home, this is useful for protecting yourself and your family from exposure to cigarette smoke, 3) When you are in a public place, such as an office, cafe or restaurant, choose a room that is smoke-free, 4) Use a mask regularly. correctly when leaving the house to avoid exposure to cigarette smoke, 5) Politely remind smokers who smoke anywhere.